Lipocalin-type prostaglandin D synthase levels increase in patients with narcolepsy and idiopathic hypersomnia. Issue 4 (11th November 2020) - Wang, Peipei; Li, Qinghua; Dong, Xiaosong; An, Haiyan; Li, Jing; Zhao, Long; Yan, Han; Aritake, Kosuke; Huang, Zhili; Strohl, Kingman P; Urade, Yoshihiro; Zhang, Jun; et al.
Abstract: Study Objectives: Excessive daytime sleepiness (EDS) is a frequent cause for consultation and a defining symptom of narcolepsy and idiopathic hypersomnia (IH). The associated mechanisms remain unclear. Lipocalin-type prostaglandin D synthase (LPGDS) is a plausible sleep-inducing candidate. This study is to compare cerebral spinal fluid (CSF) and serum LPGDS levels in patients group with hypersomnia of central origin, including those with narcolepsy type 1 (NT1) and type 2 (NT2) and IH, to those in healthy controls (Con). Methods: Serum LPGDS, CSF LPGDS, and CSF hypocretin-1(Hcrt-1) levels were measured by ELISA in 122 narcolepsy patients (106 NT1 and 16 NT2), 27 IH, and 51Con. Results: LPGDS levels in CSF ( p = 0.02) and serum ( p < 0.001) were 22%–25% lower in control subjects than in patients with EDS complaints, including NT1, NT2, and IH. In contrast to significant differences in CSF Hcrt-1 levels, CSF L-PGDS levels and serum L-PGDS were comparable among NT1, NT2, and IH ( p > 0.05), except for slightly lower serum LPGDS in IH than in NT1 ( p = 0.01). Serum L-PGDS correlated modestly and negatively to sleep latency on MSLT ( r = −0.227, p = 0.007) in hypersomnia subjects. Conclusions: As a somnogen-producing enzyme, CSF/serum LPGDS may serve as a new biomarker for EDS of central origin and imply a common pathogenetic association, but would complement rather than replaces orexin markers.